2013
DOI: 10.1080/08993408.2013.777236
|View full text |Cite
|
Sign up to set email alerts
|

Mobile game development: improving student engagement and motivation in introductory computing courses

Abstract: Computer games have been accepted as an engaging and motivating tool in the computer science (CS) curriculum. However, designing and implementing a playable game is challenging, and is best done in advanced courses. Games for mobile devices, on the other hand, offer the advantage of being simpler and, thus, easier to program for lower level students. Learning context of mobile game development can be used to reinforce many core programming topics, such as loops, classes, and arrays. Furthermore, it can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 49 publications
5
20
0
Order By: Relevance
“…The pattern of these results provides strong evidence that the inclusion of GameMaker in the classroom impacted overall attitudes toward computer science. These results are similar to those reported by Kurkovsky [23] who found that students who developed mobile game modules in an introductory CS course showed a higher level of engagement than students who did not develop game modules. We found only one interaction between condition and gender of participant.…”
Section: Copyright © 2015 Mecssupporting
confidence: 81%
“…The pattern of these results provides strong evidence that the inclusion of GameMaker in the classroom impacted overall attitudes toward computer science. These results are similar to those reported by Kurkovsky [23] who found that students who developed mobile game modules in an introductory CS course showed a higher level of engagement than students who did not develop game modules. We found only one interaction between condition and gender of participant.…”
Section: Copyright © 2015 Mecssupporting
confidence: 81%
“…Programming real systems gives additional motivation for many students and therefore the natural connection between ICT and mechatronics can benefit the ICT curricula. Kurkovsky (2013) [41] introduced robotics-related material into a mobile computing class and reported that students generally viewed the integration positively. At the introductory level the Lego MindStorm platform and recent popular platforms such as Arduino, Robotic HomeLab and even Raspberry Pi offer good possibilities for integrating ICT knowledge with interdisciplinary applications.…”
Section: ) Interdisciplinary Integrationmentioning
confidence: 99%
“…Providing an example of a challenging learning activity, Lee, Ko and Kwan [10] embedded assessment into an educational computer game designed to teach programming. In another example, Kurkovsky [9] used mobile game development to motivate and enthuse students in an introductory programming course. These studies all report success in increasing students' participation in the learning activities.…”
Section: Motivations For Improving Student Engagementmentioning
confidence: 99%